A comparison of neonatal outcomes after taking progesterone pills and progesterone intramuscular injections in preterm labor: An RCT - Maryam Dalili; Moeeneh Barkhori-Mehni; Fatemeh Karami Robati (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Approximately two-thirds of infant mortality within the first year of life are caused by preterm labor (PL). Objective: This study aimed to investigate the effects of progesterone-based compounds to prevent PL. Materials and Methods: This randomized clinical trial study was conducted on 146 pregnant women admitted to Department of Obstetrics and Gynecology, Afzalipour hospital in Kerman University of Medical Sciences, Kerman, Iran in June 2019. The participants with PL received Tocolytic and 12 mg Betamethasone in 2 doses over 2 days to mature the fetus's lungs. Stopping PL was considered a 12-hr period without any contractions after finishing the Tocolytic. Following the successful cessation of PL, the participants were monitored for 48 hr. Subsequently, the participants were divided into 2 groups. Participants received 200 mg Lutogel capsules orally per day in group A while group B received a weekly dose of 250 mg Proluton in the form of intramuscular injection, respectively. Treatment in groups continued until the 36 th wk of delivery. The participants were followed-up weekly, and if any signs of PL were detected, an obstetrician carried out a vaginal examination. Results: The incidence of PL was the same in both groups. There was no significant difference in the latent phase, average birth weight, and the neonatal intensive care unit admission frequency (p = 0.07, 0.17, 0.58, respectively) between groups. Conclusion: No difference in the results obtained from theneonataloutcomes evaluated in groups. Both medications similarly led to recovering pregnancy and neonatal outcomes caused by PL. Applying the oral form with similar beneficial effects were pointed out in this study, which can be a solution to the issues caused by numerous injections that are inevitable in the injected administration of this medicine.